Forecasting Of Production And Export Indonesian Pepper Commodities Using Smoothing Exponential And Holt Winter Methods - Hapiz Jasman; Eman Lesmana; Julita Nahar (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: The last few years the contribution of Indonesian pepper in the world market has decreased and has been replaced by Vietnam. If in 2000 and a few years before Indonesia became the world’s main pepper exporter, since 2001 the position has been replaced by Vietnam. In 2006 Indonesia’s position fell back to number three the world was replaced by Brazil which was ranked second. In 2006 Indonesian exports outperformed brazil and returned to rank second. Based on data from the Directorate General of Plantations in 2015, the area under pepper in Indonesia tends to decrease from 2004 to 2015 with an average reduction of area of 3064.5 hectares per year. Based on data from the Directorate General of Plantation in 2015, the area of pepper in Indonesia tends to decline from 2004-2015 with an average reduction of 3,064.5 hectares per year. The occurrence of the deduction according to the Ministry of Agriculture (2013), among others, is caused by: (a) drought; (b) Pest and disease attacks, especially stem rot and jaundice; and (c) conversion of pepper into mining or other plantation land, such as oil palm, rubber or cocoa. Design/methodology/approach:. Methods used to predict the number of production and consumption of domestic and export of Indonesian pepper is Double exponential Smoothing Brown and the Smoothing exponential method of Holt-Winter. Research limitations/implications: This Paper discusses the predictions of production and domestic consumption and the export of Indonesian pepper.